Criticism of the Classical Theory of Macroeconomic Modeling - Kumehov, K. K. (Vestnik MGIMO-Universiteta, 2015)
Current approaches and methods of modeling of macroeconomic systems do not allow to generate research ideas that could be used in applications. This is largely due to the fact that the dominant economic schools and research directions are building their theories on misconceptions about the economic system as object modeling, and have no common methodological approaches in the design of macroeconomic models. All of them are focused on building a model aimed at establishing equilibrium parameters of supply and demand, production and consumption. At the same time as the underlying factors are not considered resource potential and the needs of society in material and other benefits. In addition, there is no unity in the choice of elements and mechanisms of interaction between them. Not installed, what are the criteria to determine the elements of the model: whether it is the institutions, whether the industry is whether the population, or banks, or classes, etc. From the methodological point of view, the design of the model all the most well-known authors extrapolated to the new models of the past state or past events. As a result, every time the model is ready by the time the situation changes, the last parameters underlying the model are losing relevance, so at best, the researcher may have to interpret the events and parameters that are not feasible in the future. In this paper, based on analysis of the works of famous authors, belonging to different schools and areas revealed weaknesses of their proposed macroeconomic models that do not allow you to use them to solve applied problems of economic development. A fundamentally new approaches and methods by which it is possible the construction of macroeconomic models that take into account the theoretical and applied aspects of modeling, as well as formulated the basic methodological requirements.